Two-year survival with nivolumab in previously treated advanced non–small-cell lung cancer: A real-world pooled analysis of patients from France, Germany, and Canada. (July 2021) - Debieuvre, Didier; Juergens, Rosalyn A.; Asselain, Bernard; Audigier-Valette, Clarisse; Auliac, Jean-Bernard; Barlesi, Fabrice; Benoit, Nicolas; Bombaron, Pierre; Butts, Charles A.; Dixmier, Adrien; Gröschel, Andreas; Gutz, Sylvia; et al.
Highlights: Median overall survival (OS) was 11.3 months and similar across the 3 countries. OS rates were 49 % at 1 year and 28 % at 2 years for the total study population. OS rates were ≈20 % at 2 years in ECOG PS ≥ 2, liver, and bone metastasis subgroups. Median OS and OS rates were independent of age and prior lines of therapy. Nivolumab effectiveness in real-world settings was consistent with phase 3 trials. Abstract: Objectives: Immune checkpoint inhibitors have become the standard of care for metastatic non–small-cell lung cancer (NSCLC) progressing during or after platinum-based chemotherapy. Real-world clinical practice tends to represent more diverse patient characteristics than randomized clinical trials. We sought to evaluate overall survival (OS) outcomes in the total study population and in key subsets of patients who received nivolumab for previously treated advanced NSCLC in real-world settings in France, Germany, or Canada. Materials and methods: Data were pooled from two prospective observational cohort studies, EVIDENS and ENLARGE, and a retrospective registry in Canada. Patients included in this analysis were aged ≥18 years, had stage IIIB/IV NSCLC, and received nivolumab after at least one prior line of systemic therapy. OS was estimated in the pooled population and in various subgroups using the Kaplan-Meier method. Timing of data collection varied across cohorts (2015–2019). Results: Of the 2585 patients included in this analyses, 1235 (47.8 %) were treated in France, 881 (34.1 %) in Germany, and 469 (18.1 %) in Canada. Median OS for the total study population was 11.3 months (95 % CI: 10.5–12.2); this was similar across France, Germany, and Canada. The OS rate was 49 % at 1 year and 28 % at 2 years for the total study population. In univariable Cox analyses, the presence of epidermal growth factor receptor mutations in nonsquamous disease, liver, or bone metastases were associated with significantly shorter OS, whereas tumor programmed death ligand 1 expression and Eastern Cooperative Oncology Group performance status 0–1 were associated with significantly prolonged OS. Similar OS was noted across subgroups of age and prior lines of therapy. Conclusion: OS rates in patients receiving nivolumab for previously treated advanced NSCLC in real-world clinical practice closely mirrored those in phase 3 studies, suggesting similar effectiveness of nivolumab in clinical trials and clinical practice.